HOP PRODUCTION - WORLD AND UKRAINIAN MARKETS - RATOSHNIUK, TATIANA; RATOSHNIUK, VIKTOR (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article highlights the current problems of hop development in the world, trends and directions of stabilization of the Ukrainian industry for the production of competitive and quality products. An analysis of the current state and further development of world and Ukrainian hop production, identified the main producers of hop products, analyzed the area of hop plantations, yields, gross harvest, varietal composition, world beer production and the need for α-acids. Problems of Ukrainian hop growing are outlined. Before bringing hop products to the world market there are a number of tasks that need to be implemented: ensuring the implementation of competitive advantages of the hop industry of Ukraine - human, resource, geographical, innovative, scientific, geopolitical, infrastructural potential; increase production and improve its quality according to world standards; intensification of investment processes, giving them an innovative focus; growing influence of foreign direct investment; ensuring the growth of domestic market capacity by increasing household incomes and profits of enterprises in the industry; growth of hop production and improvement of export structure.